Glycated albumin for glycemic control of diabetic patients on hemodialysis - Alvina Alvina (Faculty of Medicine, Universitas Trisakti, 2014)
Regular assessment of glycemic control in diabetic patients is very important, because it reduces the incidence of complications and determines prognosis and quality of life of the patients.(1) Uncontrolled and advanced diabetes may lead to complications, such as kidney disease, heart attacks, and stroke, which are on the increase worldwide. Patients with diabetic nephropathy account for almost 50% of dialysis patients in the US, while cardiovascular disease is the main cause of death of patients with complicated diabetes.(2)